Correlation between central and uterine hemodynamics in hypertensive disorders of pregnancy. (9th July 2019) - Perry, H.; Lehmann, H.; Mantovani, E.; Thilaganathan, B.; Khalil, A.
ABSTRACT: Objective: Pregnancies affected by a hypertensive disorder (HDP) have increased uterine artery pulsatility index (UtA‐PI) compared with that in healthy pregnancies. Women with HDP are also known to have lower cardiac output and increased systemic vascular resistance. The aim of this study was to investigate the relationship between central and uterine hemodynamics in HDP and uncomplicated pregnancy. Methods: This was a prospective study of HDP and normotensive control singleton pregnancies presenting at a tertiary referral hospital between January 2012 and December 2017. Paired measurements of maternal hemodynamics, using a non‐invasive device (USCOM‐1A®), and UtA‐PI were performed in the third trimester. HDP pregnancies were divided into preterm (onset < 37 weeks' gestation) and term (onset ≥ 37 weeks). Spearman's rank coefficient was used to assess the correlation between the central and uteroplacental hemodynamics. Regression analysis was performed to assess the association of UtA‐PI with independent variables. Results: We included 231 women with HDP (152 with preterm and 79 with term HDP) and 378 controls with normotensive pregnancy. Compared with controls, women with preterm HDP had significantly lower cardiac output (median (interquartile range (IQR)), 6.0 (5.1–7.2) vs 6.6 (5.8–7.5) L/min; P < 0.001) and significantly higher systemic vascular resistance (median (IQR), 1394 (1189–1670) vs 1063 (915–1222) dynes × s/cm 5 ; P < 0.001) and UtA‐PI (median (IQR), 1.0 (0.75–1.4) vs 0.67 (0.58–0.83); P < 0.001). Conversely, in women with term HDP, there were no significant differences in heart rate, cardiac output or UtA‐PI compared with controls (all P > 0.05), while systemic vascular resistance was significantly higher (median (IQR), 1315 (1099–1527) vs 1063 (915–1222) dynes × s/cm 5 ; P < 0.001). On multiple regression analysis, heart rate, mean arterial pressure and stroke volume were associated significantly with mean UtA‐PI (all P < 0.001). Conclusions: Differences observed between HDP and normotensive pregnancies in third‐trimester UtA resistance are mirrored in the central maternal hemodynamic parameters. Late pregnancy differences in the uteroplacental circulation in preterm and term HDP are an index of maternal cardiovascular function rather than being related to inadequate spiral artery remodeling and impaired placentation. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.